2001
DOI: 10.1068/c12m
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships, Power, and Scale in Rural Governance

Abstract: Partnerships have become established as a significant vehicle for the implementation of rural development policy in Britain. In promoting new working relationships between different state agencies and between the public, private, and voluntary sectors, partnerships have arguably contributed to a reconfiguration of the scalar hierarchy of the state. In this paper we draw on recent debates about the ‘politics of scale’ and on empirical examples from Mid Wales and Shropshire to explore the scalar implications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(72 citation statements)
references
References 29 publications
1
69
0
2
Order By: Relevance
“…Whilst catchments are primarily presented as natural hydrological units, their 'naturalness' also has political implications. It is hardly a novel observation that natural units cut across political and administrative boundaries and the primacy given to the 'natural' boundaries in the catchment approach is consistent with new cross-cutting forms of partnership governance (Edwards et al, 2001). The catchment approach gives rise to both new modes of political engagement within catchment governance (Kallis et al, 2006) and 7 new partnerships which may also serve to undermine pre-existing jurisdictions as has been shown, for example, in the US context by Maddock (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst catchments are primarily presented as natural hydrological units, their 'naturalness' also has political implications. It is hardly a novel observation that natural units cut across political and administrative boundaries and the primacy given to the 'natural' boundaries in the catchment approach is consistent with new cross-cutting forms of partnership governance (Edwards et al, 2001). The catchment approach gives rise to both new modes of political engagement within catchment governance (Kallis et al, 2006) and 7 new partnerships which may also serve to undermine pre-existing jurisdictions as has been shown, for example, in the US context by Maddock (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Hall and Stern (2009) described the reluctance of a rural community in Ontario to fully engage in regional collaboration, instead seeking to maintain more direct lines of access to provincial and federal government funding. Poorer communities may not always benefit from participation in regional collaboration (Hall and Stern, 2009) as the "geometry of power" within regions may empower some localities or interests while marginalizing others (Edwards, Goodwin, Pemberton, and Woods, 2001). In their examination of rural governance in Wales, Edwards et al (2001) found that some regional partnerships actually strengthened the position or power of the state rather than localities or communities, while others empowered local groups and community development by opening up access to resources regionally.…”
Section: Scale As An Organizing Concept For Connecting Placesmentioning
confidence: 99%
“…Many commentators, focusing on specific examples of rural partnerships, have suggested that there has been little change in the power relationships, with the state maintaining a high degree of control on the pattern of development (see for example Murdoch and Abram, 1998, Jones and Little, 1999, Storey, 1999. This has led Edwards et al (2001) to argue that the partnership approach merely marks a shift in the strategy of the state to render society governable, rather than marking a change in governance. The same authors conclude that a reason why power has not been transferred away from the state is because partnerships have no direct accountability to the public.…”
Section: Introductionmentioning
confidence: 99%
“…Edwards et al (2001) explicitly identify accountability as a central issue in the way power is distributed and…”
Section: Accountability Requirements and The Funding Processmentioning
confidence: 99%
See 1 more Smart Citation